Yield Performance of Fine Aromatic Rice in Response to Variety and Level of Nitrogen (Journal of Environmental Science and Natural Resources, 2016)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during June to December 2014 with a view to finding out the effect of variety and level of nitrogen on the yield performance of fine aromatic rice. The experiment consisted of three varieties viz. Kalizira, Binadhan-13 and BRRI dhan34, and six levels of nitrogen viz. 0, 30, 60, 90 kg N ha-1, USG 1.8 g 4 hills-1 (55 kg N ha-1) and USG 2.7 g 4 hills-1 (80 kg N ha-1). The experiment was laid out in a randomized complete block design with three replications. Variety, level of nitrogen and their interaction significantly influenced the yield of aromatic rice. The highest grain yield (3.33 t ha-1) was obtained from Binadhan-13 followed by BRRI dhan34 (3.16 t ha-1) and the lowest grain yield was found in Kalizira (2.11 t ha-1). In case of N, the tallest plant (140.3 cm), highest number of effective tillers hill-1 (11.40), grains panicle-1 (152.8), and grain yield (3.32 t ha-1) were obtained when fertilized with USG 1.8 g 4 hills-1 and the lowest values were found in 0 kg N ha-1. Therefore, Binadhan-13 fertilized with USG 1.8 g 4 hills-1 (55 kg N ha-1) appeared as the promising practice for appreciable grain yield.J. Environ. Sci. & Natural Resources, 9(1): 41-45 2016